ANALISIS POTENSI PERTUMBUHAN EKONOMI DI KABUPATEN PROBOLINGGO TAHUN 2011-2015 - Sahiratul Himmah; Muhammad Firdaus; Farid Wahyudi (RELASI : JURNAL EKONOMI, 2018)
The research objective are: (1) to analyze the development of GDP for 5 years in each sector, (2) to analyze the economic base sectors that can promote economic growth territory and, (3) to analyze economic sectors that have potential to be developed as supporting economic growth in Probolinggo Regency. The tools used GDP growth analysis, Location Quotient (LQ) analysis, Shift Share analysis and Klassen Tipologi. The results showed the transport and communications sector is the highest growth sector in Probolinggo Regency and Agriculture, electricity, and water and services into potential sectors in Probolinggo Regency. The growth rate of the agricultural sector, the sector of excavation, and electricity and water supply sector is faster than GDP of the East Java.The agricultural sector and the electricity and water sector are excellent sectors of good potential, while the services sector is a sector with good value potential. Keywords: Analysis, Economic Growth